A Dual-Polarized Dual-Band Patch Antenna Based on Orthogonal Modes Manipulation. (18th July 2022) - Liu, Run; Tian, Xiaoqing; Sima, Boyu; Sun, Zhiwei; Yu, Yantao; Cao, Hailin
Abstract : In this paper, a co-caliber structure for dual-polarized dual-band (DPDB) radiation is presented through cross-polarized modes manipulation. After introducing slots and a connection branch into a typical patch antenna, two orthogonal radiation modes with different electrical-length achieved a meandered current mode at the lower frequency and a patch radiation mode at the higher frequency. The radiation patterns at both frequencies are patch-like, benefitting from certain feeding designs. The dual frequencies can be manipulated independently since their working modes are independent. In addition, compared with the traditional patch, the proposed antenna performs a higher aperture efficiency with a miniaturized antenna dimension. The antenna is finally fabricated and measured. The measured results showed that the antenna is evidently cross-polarized working at 10.38 GHz and 14.2 GHz and the gains are 5.57 dB and 6.82 dB, respectively. With the advantages of being compact, easily fabricated, and integrated, the proposed antenna can be potentially utilized in antenna research, polarization manipulation, multichannel communication system, and so on.